2009
DOI: 10.2527/jas.2009-2184
|View full text |Cite
|
Sign up to set email alerts
|

Effect of wheat forage maturity and preservation method on forage chemical composition and performance of growing calves fed mixed diets12

Abstract: Three 2.4-ha wheat (Triticum aestivum L.) fields were used to test the effects of maturity at harvest (boot vs. dough) and preservation method (hay vs. silage) on forage yield, chemical composition, and animal performance when fed in mixed diets. Forages were incorporated into 4 diets in a 2 x 2 factorial arrangement of treatments with hominy feed, soybean hulls, and cottonseed meal as the primary concentrate ingredients. In Exp. 1 diets contained 20% wheat forage (DM basis) and were fed to 96 beef calves (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
2
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 22 publications
3
18
2
4
Order By: Relevance
“…Similarly, Ettala et al (1990) reported higher daily growth rate of dairy heifers on silage group compared to those on hay group. On the contrary of the findings of the studies, Dennis et al (2012) observed higher average daily gain (9.8 %) in favor of young females fed dry hay compared to heifers consumed silage, while Beck et al (2009) reported insignificant difference regarding weight gains between heifers fed silage or hay rations. However, the effect of the breeds of heifers did not result in significant difference in terms of total weight gain (Table 4).…”
Section: Figure 1 Live Weights (Kg) Of the Heifers At 15 Days Intervcontrasting
confidence: 54%
See 2 more Smart Citations
“…Similarly, Ettala et al (1990) reported higher daily growth rate of dairy heifers on silage group compared to those on hay group. On the contrary of the findings of the studies, Dennis et al (2012) observed higher average daily gain (9.8 %) in favor of young females fed dry hay compared to heifers consumed silage, while Beck et al (2009) reported insignificant difference regarding weight gains between heifers fed silage or hay rations. However, the effect of the breeds of heifers did not result in significant difference in terms of total weight gain (Table 4).…”
Section: Figure 1 Live Weights (Kg) Of the Heifers At 15 Days Intervcontrasting
confidence: 54%
“…Heifers in the HCS program had heavier body weights than those in the HDH program in the second half of the feeding period, but the difference of the body weights at various stages of the growth was not statistically significant (Figure 1). Similarly, Beck et al (2009) reported that heifers reared on silage program had nearly the same body weights as those reared on dry hay group.…”
Section: Trialmentioning
confidence: 97%
See 1 more Smart Citation
“…Ao passo que a planta avança em estádios de maturação a produção de matéria seca tende a aumentar (David et al, 2010, Beck et al, 2009; porém, ocorre redução nos teores de proteína bruta (Fontaneli et al, 2009 de pré-florescimento quanto no estádio de grão farináceo, porém, cada qual com suas peculiaridades estruturais e químicas. O estádio de pré-florescimento é caracterizado pela elevada concentração de proteína bruta, baixo teor de matéria seca e fibra de alta digestibilidade (Filya, 2003).…”
Section: Estádio De Colheita De Cereais De Inverno Para Silagem Pré-sunclassified
“…However, the benefits of higher nutritive value and earlier harvest date at the booting stage are offset by lower dry matter (DM) production compared to harvesting at the dough stage (1)(2)(3). Maturity differences among species also have a great impact on their nutritive value (1).…”
Section: Introductionmentioning
confidence: 99%